2020
DOI: 10.21203/rs.2.22549/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic polymorphism of Plasmodium falciparum circumsporozoite protein on Bioko Island, Equatorial Guinea and global comparative analysis

Abstract: Background Plasmodium falciparum circumsporozoite protein (PfCSP) is a potential malaria vaccine candidate, but various polymorphisms of the pfcsp gene among global P. falciparum population become the major barrier to the effectiveness of vaccines. This study aimed to investigate the genetic polymorphisms and natural selection of pfcsp in Bioko and the comparison among global P. falciparum population.Methods From January 2011 to December 2018, 148 blood samples were collected from P. falciparum infected Bioko … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…Overall, with the polymorphism analysis, Bioko PfTRAP exhibited the high polymorphism, which is consistent with PfTRAP from other African countries but signi cantly distinct with the relatively low polymorphic Asian PfTRAP. These phenomena consistence with our previous report about Plasmodium falciparum circumsporozoite protein (PfCSP) gene [28], which also indicated that the similar polymorphic pattern between Bioko and Africa mainland countries. Moreover, our team had carried out the exploration and analysis of other vaccine candidate genes previously, including pre-erythrocytic stage CSP gene, erythrocytic phase merozoite surface protein (MSP-1/2) and asexual blood stage apical membrane antigen-1 (AMA-1) gene [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, with the polymorphism analysis, Bioko PfTRAP exhibited the high polymorphism, which is consistent with PfTRAP from other African countries but signi cantly distinct with the relatively low polymorphic Asian PfTRAP. These phenomena consistence with our previous report about Plasmodium falciparum circumsporozoite protein (PfCSP) gene [28], which also indicated that the similar polymorphic pattern between Bioko and Africa mainland countries. Moreover, our team had carried out the exploration and analysis of other vaccine candidate genes previously, including pre-erythrocytic stage CSP gene, erythrocytic phase merozoite surface protein (MSP-1/2) and asexual blood stage apical membrane antigen-1 (AMA-1) gene [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…These phenomena consistence with our previous report about Plasmodium falciparum circumsporozoite protein (PfCSP) gene [28], which also indicated that the similar polymorphic pattern between Bioko and Africa mainland countries. Moreover, our team had carried out the exploration and analysis of other vaccine candidate genes previously, including pre-erythrocytic stage CSP gene, erythrocytic phase merozoite surface protein (MSP-1/2) and asexual blood stage apical membrane antigen-1 (AMA-1) gene [28][29][30]. These results shown that the polymorphism of candidate genes associated with malaria vaccines in Africa has been at a high level for a long time.…”
Section: Discussionsupporting
confidence: 91%